Synthesis and evaluation of lanthana modified Cu-based catalysts for CO2 hydrogenation to value added products - Sardar, Ali (2023)
This study deals with the development and evaluation of lanthana promoted Cu-based catalysts for CO2 hydrogenation reaction. The samples were prepared using solution combustion synthesis method. The study demonstrates that the incorporation of 3wt% lanthana (La2O3) into a CuO/ZnO/Al2O3 results in a catalyst with exceptionally high catalytic performance. The synthesized catalysts were thoroughly characterized by various analytical tools such as HRTEM, XRD, XPS, H2-TPR, H2-TPD and CO2-TPD. The catalysts were assessed for CO2 hydrogenation reaction in a high-pressure fixed-bed reactor. The La2O3 promoted catalyst with a composition of 0.6Cu/0.3ZnO/0.03La2O3/0.07Al2O3 was selective to methanol (60%) even at an operating temperature as high as 325 °C and an operating pressure of 85 bars. Under similar operating conditions, the 0.6Cu/0.3ZnO/0.03La2O3/0.07Al2O3 catalyst exhibited better CO2 conversion, MeOH selectivity and MeOH production as compared to unpromoted catalyst, 0.6Cu/0.3ZnO/0.1Al2O3. At reaction conditions of T = 300 °C, P = 85 bar, and GHSV=55,000h-1, the lanthana promoted catalyst showed a CO2 conversion and methanol selectivity of 20% and 65%, respectively; while the production rates of carbon monoxide and methanol were 0.55 g/g-cat h−1 and 0.79 g/g-cat h−1. The high catalytic efficiency is attributed to the formation of oxygen vacancies and/or generation of defects in the catalyst surface, smaller Cu nanoparticles with LaOx, and a comparable larger number of mild basic sites. Similar catalyst prepared by wet impregnation method performed poorly, thus highlighting the role of combustion synthesis and the effect of temperature in forming unique metal oxide phases responsible for higher catalytic performance.